The effects of nutrition bio-shield superfood powder on immune system function: A clinical trial study among patients with COVID-19 - Azizi Jalilian, Farid; Keshavarz, Gheisar; Khazaei, Salman; Nezamdoost, Manije; Hashemi, Seyed Hamid; Mamani, Mojgan; Ansari, Nastaran; Amini, Razieh; Khalkhali, Aref; Keshavarz, Arghavan; Ayubi, Erfan; Fazeli, Maryam; et al. (Frontiers in Immunology, 2022)
The present study aimed to evaluate the effects of Nutrition Bio-shield Superfood (NBS) powder on the immune system function and clinical manifestations in patients with COVID-19. We compare the effects of NBS powder on the immune system function and clinical manifestations among two different groups: 1) intervention group receiving standard treatment scheduled according to treatment guidelines plus NBS powder, and 2) control group receiving only the same standard treatment. The serum levels of IL-2, IL-6, IL-17, IFNγ, and TNFα were determined after four weeks of treatment by specific ELISA kits according to the manufacturer’s instructions. Finally, the level of immune system stimulation and inflammatory markers were compared at baseline and after intervention in both groups. Data were analyzed using SPSS (version 22). A p-value of ≤ 0.05 was set as significant. A total of 47 patients with COVID-19 (24 patients in the intervention group and 23 patients in the control group) were included in this study. Results showed that the differences in the mean decrease of IL-2, IL-6, and TNF-α in the intervention group in comparison to the control group were 0.93, 10.28, and 8.11 pg/ml, respectively (P<0.001). On the other hand, there was no difference in IL-17, IFNγ, monocytes, eosinophil, and other inflammatory indices between the intervention and control groups. Although NBS powder was able to significantly decrease the levels of some proinflammatory cytokines in patients with COVID-19, however, it is noteworthy that the course of the disease was to large part unaffected by NBS power and there was a reduction independent of treatment. The present study indicates that NBS powder could provide a beneficial anti-inflammatory effect in patients with COVID-19. Hence, NBS in treating patients with COVID-19 shows promise as an adjuvant to the current standard antiviral treatment of such patients. Clinical Trial Registration https://www.irct.ir, identifier IRCT20200426047206N1.